2014
DOI: 10.5114/kitp.2014.43849
|View full text |Cite
|
Sign up to set email alerts
|

FORUM MŁODYCH Isolated coronary artery bypass grafting in extracorporeal circulation in patients over 65 years old – does age still matter?

Abstract: IntroductionCoronary artery bypass grafting (CABG) is conducted more and more commonly in patients in advanced age.Aim of the studyTo analyze the influence of age and concurrent risk factors on the complications and early mortality after CABG.Material and methodsMedical records of 2194 patients were analyzed retrospectively. A group of 1303 patients who had undergone isolated CABG was selected. 106 (4.8%) patients were excluded due to missing data in their medical records. The remaining 1197 patients were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Such a result is in agreement with previous results [1,14]. Moreover, some authors showed that lower BSA is also a risk factor of higher drainage [4]. We have found that patients, whom BSA was noted in the first deciles, had higher drainage than those found in the last ones.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Such a result is in agreement with previous results [1,14]. Moreover, some authors showed that lower BSA is also a risk factor of higher drainage [4]. We have found that patients, whom BSA was noted in the first deciles, had higher drainage than those found in the last ones.…”
Section: Discussionsupporting
confidence: 93%
“…This affects final clinical outcome of treatment as patients undergoing re-exploration due to postoperative bleeding have higher mortality and longer hospitalization [1,4,5]. To achieve reliable results we eliminated two risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 This fragility contributes to several intra-and postoperational risks. 26 In turn, this leads to more physicians favoring less invasive treatments due to concerns that complex procedures would lead to poorer outcomes when combined with these patients' frailty.…”
Section: Cad In Patients Between 60 and 80 Yearsmentioning
confidence: 99%